HUBUNGAN MASA KERJA DAN USIA DENGAN TINGKAT HIDRASI PEKERJA PERAJIN MANIK-MANIK DI KABUPATEN JOMBANG - Neffrety Nilamsari; Ratih Damayanti; Erwin Dyah Nawawinetu (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2018)
Every workplace always has potential hazards. The potential hazards most often found inmanufacturing industries are potential physical hazards that can affect labor productivity. The purposeof this study was to analyze the relationship between working period and age of bead craftsmen withhydration levels. Respondents in this study were 19 workers in PT X Jombang Regency. This researchis an observational study with a cross sectional design. Data collection was conducted from April toJuly 2018. Statistical tests used correlation test in testing urin color indications to determinedehydration levels. The results showed a relationship between the variable work period and the level oflabor hydration with p-value 0.000, age variable with hydration level did not have a relationship withp-value 0.087 where the temperature in the workspace averages 34.1°C. There is a relationship betweenthe length of work and the level of hydration of bead craftsmen and there is no relationship betweenage and level of hydration of bead craftsmen. To reduce the level of hydration status, it isrecommended that every bead craftsman every 2 hours drink as much as 0.5 liters of water, so that theneed for fluids is approximately 2 liter in 8 hours of work can be fulfilled. Companies are advised toadd the amount of ventilation in the workspace to reduce exposure to hot temperatures in theworkspace. Keywords: Hydration level, working period, age